(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The article is devoted to the manifestation of speech aggression and some types and forms of its manifestation. Verbal aggression is relevant at the present stage, knowing the forms of its manifestation, it is possible to prevent verbal aggression at various stages of manifestation and ways to overcome it.